L’argomento “ad hominem”: riflessioni sulle funzioni della violenza verbale (Altre Modernità, 2010)
The aim of this paper is to argue that the attack against someone else, as a kind of argument ad hominem, has a civic utility when it gives issue to polemic antagonism. Verbal violence can therefore be seen as functional: a way to express dissension within society and to regulate it. In opposition to the rhetorical search for common agreement, the ad hominem can nevertheless be studied as a discourse strategy attacking someone in order to force him to an antagonist point of view. As a public discussion, the success of this sort of argument relies on the agreement of the group and then on its adequacy to formal rules of social interaction, no matter how manipulated the polemic argument could be. The ethical perspective is thus the very question to be considered in analysing the ad hominem strategy. Its utility as a regulation of violence through its moving on the ground of verbal confrontation couldn't in any way legitimate the fact that polemic expression turns into physical violence or even suggests it, disrupting the thin space where violence can be expressed, by argumentation, as a passionate but regulated antagonism.